2014
DOI: 10.1098/rspb.2014.0619
|View full text |Cite
|
Sign up to set email alerts
|

Novel biopesticide based on a spider venom peptide shows no adverse effects on honeybees

Abstract: Evidence is accumulating that commonly used pesticides are linked to decline of pollinator populations; adverse effects of three neonicotinoids on bees have led to bans on their use across the European Union. Developing insecticides that pose negligible risks to beneficial organisms such as honeybees is desirable and timely. One strategy is to use recombinant fusion proteins containing neuroactive peptides/proteins linked to a ‘carrier’ protein that confers oral toxicity. Hv1a/GNA (Galanthus nivalis agglutinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 42 publications
0
46
0
2
Order By: Relevance
“…Some spider toxins have extreme taxonomic selectivity within Insecta; for example some spider knottins kill German cockroaches ( Blattellla germanica ) but not the closely related American cockroach Periplaneta americana . Moreover, several spider knottins have been isolated that kill a broad range of insect pests but are harmless to bees and beneficial parasitoids, including ω‐hexatoxin‐Hv1a and ω/κ‐hexatoxin‐Hv1a (Spear®), the knottin peptide that has been developed by Vestaron Corporation for control of insects and mites…”
Section: Can Spider Knottins Be Developed As Insecticides?mentioning
confidence: 99%
“…Some spider toxins have extreme taxonomic selectivity within Insecta; for example some spider knottins kill German cockroaches ( Blattellla germanica ) but not the closely related American cockroach Periplaneta americana . Moreover, several spider knottins have been isolated that kill a broad range of insect pests but are harmless to bees and beneficial parasitoids, including ω‐hexatoxin‐Hv1a and ω/κ‐hexatoxin‐Hv1a (Spear®), the knottin peptide that has been developed by Vestaron Corporation for control of insects and mites…”
Section: Can Spider Knottins Be Developed As Insecticides?mentioning
confidence: 99%
“…However, recent declines in pollinator populations have affected global agricultural production and impacted both food production and the economy (Potts et al 2010). One of the probable causes for the population declines of pollinators, including honeybees, is the indiscriminate use of pesticides (Klein et al 2007;Potts et al 2010;Nakasu et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…These exciting results flag GNA-Hv1a as a promising candidate bioinsecticide for insect pest control, either as an alternative to harmful chemical insecticides or for trait staking or pyramiding with Bt in transgenic crops to widen the targeted pest range and to reduce the risk of resistance development. It was recently shown that an Hv1a-GNA fusion protein has no adverse effects on honeybees (Nakasu et al, 2014), which further highlights the potential of GNA/Hv1a fusion proteins as eco-friendly bioinsecticides.…”
Section: Discussionmentioning
confidence: 88%
“…Hv1a specifically targets Ca v channels in the insect CNS but is harmless to vertebrates (Fletcher et al, 1997;Tedford et al, 2004a;Tedford et al, 2004b;Chong et al, 2007). This 37-residue peptide has potent insecticidal activity in a wide range of insect orders, including Lepidoptera, Homoptera, and Diptera (Khan et al, 2006;Mukherjee et al, 2006), but it is harmless to honeybees (Nakasu et al, 2014). Thus, Hv1a is considered a strong candidate for development as a novel bioinsecticide (King, 2007a;King and Hardy, 2013;Nakasu et al, 2014).…”
Section: The Insecticidal Spider-venom Peptide ω-Hxtx-hv1amentioning
confidence: 99%
See 1 more Smart Citation